ESTIMATED UNREGORDED CATCH RELATED TO THE NUMBER OF LICENSED FISHING VESSEL IN THE ARAFURA SEA - Badrudin Badrudin; Subhat Nurhakim; Budi Iskandar Prisantoso (Indonesian Fisheries Research Journal, 2008)
The fish resources in the Arafura Sea have been intensively exploited by the industrial scale of fish trawl (flsh nef), shrimp net and bottom long line